2005
DOI: 10.1111/j.1365-313x.2005.02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid‐activated SNRK2 protein kinases function in the gene‐regulation pathway of ABA signal transduction by phosphorylating ABA response element‐binding factors

Abstract: SummaryThe plant hormone abscisic acid (ABA) induces gene expression via the ABA-response element (ABRE) present in the promoters of ABA-regulated genes. A group of bZIP proteins have been identified as ABRE-binding factors (ABFs) that activate transcription through this cis element. A rice ABF, TRAB1, has been shown to be activated via ABA-dependent phosphorylation. While a large number of signalling factors have been identified that are involved in stomatal regulation by ABA, relatively less is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
284
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 386 publications
(300 citation statements)
references
References 62 publications
14
284
0
2
Order By: Relevance
“…Given that FaSnRK2.6 is a negative regulator of strawberry fruit development and ripening, whereas OST1 is a positive regulator of stomatal movement, FaSnRK2.6 must operate via distinct mechanisms in these biological processes. Although SnRK2 protein kinases have been suggested to be downstream signal transducers of ABA (Kobayashi et al, 2005;Wang et al, 2013b) and although we found that SnRK2.6 interacts physically with FaABI1 (Fig. 6), the FaSnRK2.6-mediated regulation of strawberry fruit development and ripening likely does not Figure 9.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Given that FaSnRK2.6 is a negative regulator of strawberry fruit development and ripening, whereas OST1 is a positive regulator of stomatal movement, FaSnRK2.6 must operate via distinct mechanisms in these biological processes. Although SnRK2 protein kinases have been suggested to be downstream signal transducers of ABA (Kobayashi et al, 2005;Wang et al, 2013b) and although we found that SnRK2.6 interacts physically with FaABI1 (Fig. 6), the FaSnRK2.6-mediated regulation of strawberry fruit development and ripening likely does not Figure 9.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Kobayashi et al (2005) identified 10 SnRK2 protein kinases encoded in rice (Oryza sativa), and all of these SnRK2s were specifically activated by osmotic stress at both the transcriptional and the posttranscriptional levels. The involvement of the stress signal, FaSnRK2.6, in the regulation of fruit development and ripening may reasonably be explained from a plant ecological perspective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations